Outcomes of Ureteral Stent Removal by Flexible Cystoscope Versus Semirigid Ureteroscope: A Prospective Randomized Clinical Trial - Ketan Mehra; Neeraj Agarwal; Ramanitharan Manikandan (Journal of Urological Surgery)

(untitled)
Objective:Ureteral stents are usually removed after 2-4 weeks. Classically rigid cystoscope was used for stent removal along with retrieval forceps. A flexible cystoscope is an excellent alternative to a rigid cystoscope to reduce discomfort. In this study we compared semirigid ureteroscope with a flexible cystoscope for retrieving stents.Materials and Methods:It was a prospective randomized clinical trial including 100 patients. All patients were divided into two groups: Group A: Patients undergoing Double J stent (DJS) removal using a flexible cystoscope. Group B: Patients undergoing DJS removal using a semirigid ureteroscope. Outcome parameters compared in both groups were pain during and after the procedure, operative time, and operative difficulty.Results:There were 70 males and 30 females in the study. Mean visual analogue scores (VAS) for pain during the procedure in groups A and group B were 5.2±1.4 and 5.82±1.8 (p=0.057) and after the procedure were 1.95 and 2.25 in group A and group B, respectively (p=0.253). Mean VAS scores for pain during the procedure in males in groups A and B were 5.2±1.6 and 5.9±1.7, respectively (p=0.080). The mean operative times in groups A and group B were 4.9 and 4.2 min, respectively (p=0.076). VAS scores for operative difficulty overall were 3.6±1.1 and 2.9±1.2 (p=0.058), while in males were 3.7±1.0 and 2.8±1.3 (p=0.002) for groups A and B, respectively.Conclusion:Ureteral stents removal by semirigid ureteroscope is a good alternative as it is readily available, with the same degree of discomfort as flexible cystoscopes. They are inexpensive and easier to operate than flexible scopes.